The Effect of Government Expenditure on Infrastructure on the Growth of the Nigerian Economy, 1977-2009 - Fasoranti, Mary Modupe (International Journal of Economics and Financial Issues, 2012)
The paper examined the effects of government expenditures on infrastructure on the growth of the Nigerian economy. The data sourced majorly from the various issues of Central Bank statistical bulletin was analyzed with the aid of econometric methods. Data collected included government expenditures on education, environment and housing, health services, transport and communication, agriculture, security, inflation rate and gross domestic product. Data treatment methods used was the unit root test, co-integration and vector error correction estimation. Simple multiple regression model was used to obtain the results used for the analysis. Results showed a long run relationship between the growth of the economy and government expenditures in education, environment and housing, health services, water resources, inflation rate, agriculture, security, transport and communication. The paper observed that government expenditures on health services, transport and communication imparted negatively on growth while expenditures in agriculture and security were not significant in the growth of the economy. To increase the growth rate of the economy, the government must adopt stringent controls on its expenditures on infrastructure so as to reduce fraud, fund diversion and mismanagement. Moreover, monitoring and evaluation of government spending must be given top priority. This will help to ensure that the targets of government spending are reached. Keywords: Government expenditures; Infrastructure; Growth; Gross domestic product. JEL Classifications: EO; H5; O4